PENGARUH UKURAN PERUSAHAAN DAN PERPUTARAN PERSEDIAAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Febryanti, Siti Rini; Nurfadillah, Mursidah; Saputra, Praja Hadi (STIE Mahardhika, 2025)
This study aims to analyze the effect of company size and inventory turnover on profit growth in food and beverage companies listed on the Indonesia Stock Exchange. The study population includes consumer non-cyclical companies listed on the Indonesia Stock Exchange listed on the main board of the IDX, with a total sample of 21 companies, selected through purposive sampling techniques. This study applies a quantitative approach with secondary data analyzed using multiple linear regression methods through SPSS version 22. The findings of the analysis indicate that partially, company size does not have a significant effect on profit growth, while inventory turnover has a positive and significant effect. Simultaneously, company size and inventory turnover have a significant effect on profit growth.